Educational transformation through multimedia generative artificial intelligence: The Gemini Banana System - Sakher, Dr. Shatha; Alfawa’ra, Dr. Loiy Hamidi Qutaish (مجلة الشرق الأوسط للعلوم التربوية والنفسية, 2026)
This research presents a synthesis of the educational implications of integrating artificial intelligence (AI) within the Gemini Banana (video production) and Nano Banana (image processing) frameworks in contemporary instructional design. Using a qualitative meta-analysis methodology, this study analyzes technical documentation and empirical literature published between 2023 and 2025 to assess the potential and challenges of multimedia generative AI. The main findings indicate that these tools significantly improve the efficiency and accessibility of education by automating content creation, supporting language- and culture-sensitive instruction, and enabling rapid prototyping of educational materials. While AI-generated teachers demonstrate effectiveness in knowledge consolidation, particularly in procedural and language learning tasks (equivalence principle), they lack the social presence and empathetic interaction characteristic of human teachers. The study concludes by proposing a human-centered PATH framework (promotion, advancement, training, and harnessing) for ethical integration, and offers strategic recommendations, arguing that MGAI should serve as an enabler, not a replacement, for human teacher capacity.